Does Childhood Maltreatment Lead to Low Life Success? Comparing Agency and Self-Reports - Najman, Jake M. (Journal of interpersonal violence, 2023)
BackgroundThe long-term mental and physical health consequences of childhood maltreatment have been well documented. Less known are the longer-term consequences of childhood maltreatment, specifically the extent to which childhood maltreatment predicts adult life success.ObjectivesTo prospectively assess the extent to which childhood experiences of physical, sexual, emotional abuse and childhood neglect predict life success at 30 years of age.Participants and SettingData are from the Mater-University of Queensland Study of Pregnancy (MUSP), a pre-birth cohort study which follows children from conception to 30 years of age.MethodsDetails of childhood maltreatment are from two sources; child safety agency notifications (and substantiations) linked to the survey data with self-reports of childhood experiences of maltreatment obtained at the 30-year follow-up using the Child Trauma Questionnaire (CTQ). Life success is a 9-item composite measure (alpha = 0.76) obtained at the 30-year follow-up. We use logistic regression models (with control for covariates) to examine the association between overall as well as specific forms of childhood maltreatment on adult life success. We further test these models using different cut-offs and propensity analyses to adjust for loss to follow-up.ResultsChildhood maltreatment whether measured by agency report or self-report predicts overall low life success; agency substantiation OR = 1.88(1.14,3.08) & self-report OR = 2.60 (2.10,3.25). Self-report physical abuse, OR = 2.37(1.72,3.28); sexual abuse, OR = 2.85(2.05,3.96); emotional abuse, OR = 2.53(1.85,3.45) and neglect, OR = 2.36(1.83,3.03) all predict higher levels of low life success.ConclusionsOur findings suggest that the long-term consequences of childhood maltreatment extend to a wide range of day-to-day circumstances and extend into mid- to later life.